Study the Effect of Active Metal Loading within a γ-Alumina Support on Product Distribution in n-heptane Hydroisomerization Reactions - Khalil, Mohammed; Shakor, Zaidoon M.; Al-Zaidi, Bashir Y.; hussein, Sattar J. (Journal of Petroleum Research and Studies, 2025)
In this paper, the monofunctional acidic γ-Al2O3 catalyst was treated with Pt metals with a percentage ranging from 0.5 to 1 wt% to obtain a bifunctional nanocatalyst represented by Pt/Al2O3, for the purpose of increasing the active metal sites on its surface, and thus enhancing the extremely important hydrogenation/dehydrogenation reactions in catalyzing hydroisomerization reactions of n-heptane with an octane number of zero. Experiments were conducted in a pilot unit at a temperature of 230°C and under a pressure of 5 bar in the presence of H2-gas for the purpose of producing desirable fuel hydrocarbons with a high octane number. A number of characterization techniques, including XRD, SEM, EDX, BET and FTIR, have been used to evaluate the physical properties of the catalysts. The catalytic behavior of the prepared catalysts was compared by calculating the conversion of the hydrocarbons formed and the selectivity towards the generation of isomers in the reaction products. The comparison results indicated that the conversion, selectivity and yield track the following order according to the catalytic efficiency of the catalysts: 0.5wt% Pt/Al2O3 > 1wt% Pt/Al2O3 > γ-Al2O3. The highest conversion, selectivity, and yield were found on the surface of the 0.5wt% Pt/Al2O3 catalyst, which are 62.50, 80.96, and 50.60 wt%, respectively, while the lowest weight percentages of products were found on the surface of the unloaded-parent γ-Al2O3 catalyst, which are 52.8, 67.7, and 35.75 for conversion, selectivity, and yield, respectively. It was found that increasing the metal loading percentage from 0.5 wt% to 1 wt% causes the closure of a number of pore openings on the surface of the catalyst, which reduces the surface area. It also causes an increase in the activity of Lewis acids and rapid breakdown of the reactant hydrocarbons, thus resulting in a reduction in conversion and selectivity for isomers.